Controlling the plasmon resonance via epsilon-near-zero multilayer metamaterials - Habib Mohsin; Briukhanova Daria; Das Nekhel; Yildiz Bilge Can; Caglayan Humeyra (Nanophotonics, 2020)
Localized plasmon resonance of a metal nanoantenna is determined by its size, shape and environment. Here, we diminish the size dependence by using multilayer metamaterials as epsilon-near-zero (ENZ) substrates. By means of the vanishing index of the substrate, we show that the spectral position of the plasmonic resonance becomes less sensitive to the characteristics of the plasmonic nanostructure and is controlled mostly by the substrate, and hence, it is pinned at a fixed narrow spectral range near the ENZ wavelength. Moreover, this plasmon wavelength can be adjusted by tuning the ENZ region of the substrate, for the same size nanodisk (ND) array. We also show that the difference in the phase of the scattered field by different size NDs at a certain distance is reduced when the substrate is changed to ENZ metamaterial. This provides effective control of the phase contribution of each nanostructure. Our results could be utilized to manipulate the resonance for advanced metasurfaces and plasmonic applications, especially when precise control of the plasmon resonance is required in flat optics designs. In addition, the pinning wavelength can be tuned optically, electrically and thermally by introducing active layers inside the hyperbolic metamaterial.